Virtual Americas transnational fictions and the transatlantic imaginary - Giles, Paul (New Americanists, 2002)
Virtual subjects: transnational fictions and the transatlantic imaginary -- Narrative reversals and power exchanges: Frederick Douglass and British culture -- "Bewildering" intertanglement": Melville's engagement with British tradition -- "Changed and queer": Henry James and the surrealization of America -- From decadent aesthetics to political fetishism: the "oracle effect" of Frost's poetry -- Virtual Eden: Lolita, pornography, and the perversions of American studies -- Crossing the water: Gunn, Plath, and the poetry of passage -- Virtual Englands: Pynchon's transatlantic heresies -- Virtual Americas: cyberpastoral, transnationalism, and the ideology of exchange